2004
DOI: 10.5014/ajot.58.6.621
|View full text |Cite
|
Sign up to set email alerts
|

Functional Performance in Children With Down Syndrome

Abstract: The results provide baseline information regarding typical levels of functional performance in children with Down syndrome at 5 years of age. However, the broad range of functional performance across children indicates a need for caution in generalizing the results to an individual child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
1
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 16 publications
3
61
1
10
Order By: Relevance
“…Low score across all domains in studied participants lead to global functional affection and increased dependence on caregivers. 9 It is seen because of motor coordination impairment likewise in other developmental disorders in support to present study. Dolva AS et al analyzed functional performance in children with down syndrome using the PEDI scale showed significant lower performance skill in those children.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Low score across all domains in studied participants lead to global functional affection and increased dependence on caregivers. 9 It is seen because of motor coordination impairment likewise in other developmental disorders in support to present study. Dolva AS et al analyzed functional performance in children with down syndrome using the PEDI scale showed significant lower performance skill in those children.…”
Section: Discussionsupporting
confidence: 77%
“…Functional performance and caregivers' assistance was tested using PEDI on children with autism and Asperger syndrome8 and Down's syndrome. 9 PEDI includes 3 domains self-care, mobility and social function domain by which it quantifies functional skills and caregiver assistance. 10 So the need to perform this study was to quantify the dependence level for self-care as well as need of caregiver assistance for global functional performance in the children with PDD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the effect of sex on performance in children with Down syndrome do not lead to a firm conclusion. A study by Dolva et al, (2004) found that girls were better in some areas such as self-care skills, and that boys achieved better results on the mobility domain. It might be that the small sample in our study contributed to findings being non-significant statistically and that in larger samples the differences would be significant.…”
Section: Discussionmentioning
confidence: 99%
“…CRF also shares a positive relationship with cognitive function in the general population [9,10]. Both functional tasks of daily living and cognitive function are areas of weakness in individuals with DS [11][12][13]. However, very few exercise intervention studies were successful in improving CRF in individuals with DS [14][15][16][17][18].…”
mentioning
confidence: 99%